Biological and Electrophysiologic Effects of Poly(3,4-ethylenedioxythiophene) on Regenerating Peripheral Nerve Fibers - Baghmanli, Ziya (2013)
BACKGROUND: Uninjured peripheral nerves in upper-limb amputees represent attractive sites for connectivity with neuroprostheses because their predictable internal topography allows for precise sorting of motor and sensory signals. The inclusion of poly(3,4-ethylenedioxythiophene) reduces impedance and improves charge transfer at the biotic-abiotic interface. This study evaluates the in vivo performance of poly(3,4-ethylenedioxythiophene)–coated interpositional decellularized nerve grafts across a critical nerve conduction gap, and examines the long-term effects of two different poly(3,4-ethylenedioxythiophene) formulations on regenerating peripheral nerve fibers. METHODS: In 48 rats, a 15-mm gap in the common peroneal nerve was repaired using a nerve graft of equivalent length, including (1) decellularized nerve chemically polymerized with poly(3,4-ethylenedioxythiophene) (dry); (2) decellularized nerve electrochemically polymerized with poly(3,4-ethylenedioxythiophene) (wet); (3) intact nerve; (4) autogenous nerve graft; (5) decellularized nerve alone; and (6) unrepaired nerve gap controls. All groups underwent electrophysiologic characterization at 3 months, and nerves were harvested for histomorphometric analysis. RESULTS: Conduction velocity was significantly faster in the dry poly(3,4-ethylenedioxythiophene) group compared with the sham, decellularized nerve, and wet poly(3,4-ethylenedioxythiophene) groups. Maximum specific force for the dry poly(3,4-ethylenedioxythiophene) group was more similar to sham than were decellularized nerve controls. Evident neural regeneration was demonstrated in both dry and wet poly(3,4-ethylenedioxythiophene) groups by the presence of normal regenerating axons on histologic cross-section. CONCLUSIONS: Both poly(3,4-ethylenedioxythiophene) formulations were compatible with peripheral nerve regeneration at 3 months. This study supports poly(3,4-ethylenedioxythiophene) as a promising adjunct for peripheral nerve interfaces for prosthetic control and other biomedical applications because of its recognized ionic-to-electronic coupling potential.